Beyond Multiple Inequalities: Transversal Intersectionality, Diversity Mainstreaming and Participative Democracy - Judith Squires (The Royal Danish Library, 2010)
This article suggests that greater recognition of intersectional discrimination, understood as qualitatively distinct from the sum of its discriminatory parts, requires the adoption of a transversal rather than an additive approach to intersectionality and of mainstreaming tools in addition to anti-discrimination measures alone. In addition, it suggests that a participative-democratic form of mainstreaming offers the best resources for realising this transversal approach in practice.